2018
DOI: 10.31925/farmacia.2018.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Modulation of Melanoma Cells Proliferation

Abstract: Investigation of the complex cellular and molecular mechanisms underlying cutaneous melanoma development is of major interest in biomedical research. Within our study we have developed an in vitro experimental system using A375 human melanoma cell line to investigate the impact of adrenergic modulation in melanoma. Thus, we have studied the proliferative effect of norepinephrine and epinephrine in the absence and presence of several specific inhibitors. We have found that the pro-proliferative action of norepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This could be the first study, which other researchers and clinicians can use and analyze in order to evaluate the influence of different melanoma treatments on antiganglioside antibodies. The pathogenic mechanisms involved in melanoma are complex [ 53 55 ]; therefore, the evaluation during the follow-up period of melanoma patients at different points is needed for a better antiganglioside profile characterization.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the first study, which other researchers and clinicians can use and analyze in order to evaluate the influence of different melanoma treatments on antiganglioside antibodies. The pathogenic mechanisms involved in melanoma are complex [ 53 55 ]; therefore, the evaluation during the follow-up period of melanoma patients at different points is needed for a better antiganglioside profile characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node involvement is an important prognostic factor in the early stages [32,68]. Multiple pathways are activated in the process of tumorigenesis, metastasis and therapy resistance and phytochemicals have demonstrated beneficial effects both in the prevention and in the treatment of metastatic melanoma [15,40,53,63]. Fisetin limits melanoma cell invasiveness by modulating mitogen-activated protein kinase/extracellular signalregulated kinase 1/2 (MAPK/ERK) signalling and reducing the activation of nuclear factor-kappa B (NF-κB) pathway [41].…”
Section: Skin Melanomamentioning
confidence: 99%
“…We have shown on murine melanoma cell lines that exposure to high concentrations of epinephrine and norepinephrine induces a significant increase in cell proliferation (Caruntu(b) et al, 2014). There are different expression of specific receptors depending on the melanoma origin, thus in human melanoma cell lines we have shown that the proliferative action triggered by epinephrine and nor-epinephrine can be overridden by some of specific inhibitors (Surcel et al, 2018).…”
Section: Neuroendocrine "Influencers" Of Melanomagenesismentioning
confidence: 86%